EFEKTIVITAS METODE LATIHAN DRILL OPEN SPIKE DAN BACK ATTACK TERHADAP AKURASI SPIKE DI EKSTRAKURIKULER BOLA VOLI SMK KORPRI MAJALENGKA - Dede Triyadi Setiawan Triyadi Setiawan (STKIP Muhammadiyah Kuningan, 2023)
This study aims to determine the effectiveness of open spike drill exercises to increase accuracy, to determine the effectiveness of spike back attack drills to increase accuracy and to determine differences in the effect of drill exercises to increase open spike and spike back attack. This study uses an experimental method. The design used is a pretest-posttest control group design. The population in this study were volleyball extracurricular athletes at Korpri Majalengka Vocational School, totaling 40 members. The sampling technique used random sampling, totaling 20 athletes. The data analysis technique uses SPSS for normality, homogeneity uses the Test of Homogeneity of Variances, and t test for hypothesis testing. The results showed that the Effectiveness of Open Spike and Back Attack Drill Practice Methods on Spike Accuracy in Volleyball Extracurricular at SMK Korpri Majalengka. The results of this study are data about the pretest and posttest scores using the SPSS series 16 program with a significant level of 5%. Based on the t-test analysis, it can be seen that there is a significant effect of Drill Open Spike on Spike Accuracy. Which can be seen from the calculated significant value on the t-test of 0, 000 which is greater than 5% (sig < 0.05). Based on the research, the Drill Open Spike training model can be developed and applied in the Drill Open Spike training process in volleyball.